Patterns and Development of Islamic Education in Andalusia and Sicily - Nasril Nasril; Muhammad Yunus; Wan Mohd Yusof Wan Chik; Ahmad Iqbal Mohd Fadzli (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study examines the pattern and development of Islamic education in two critical regions of Islamic civilization in Europe: Andalusia and Sicily. This study aims to analyze the characteristics of Islamic education patterns, identify the stages of its development, and compare the dynamics of Islamic education in the two regions. Method The research uses a qualitative approach based on library research by analyzing primary and secondary sources related to the history of Islamic education in Andalusia and Sicily. Results: Research shows that the pattern of Islamic education in Andalusia is systematic and structured with a comprehensive curriculum, including religious and scientific sciences, and has formal educational institutions such as kuttab, mosques, and madrasas. Its development experienced a golden age in the era of the Umayyad Dynasty with the emergence of the University of Cordova. Meanwhile, in Sicily, Islamic education is more informal and flexible, focusing on teaching the Quran and Arabic in mosques. Its development peaked during the reign of King Roger II, who implemented a policy of tolerance and multiculturalism. A comparison of the two regions shows that Andalusia has a more established and influential education system than Sicily. However, both contribute significantly to the transfer of Islamic knowledge to Europe. Novelty: This research lies in a comprehensive comparative analysis of the characteristics and dynamics of Islamic education in the two regions, which previously tended to be studied separately. These findings provide a new perspective in understanding the contribution of Islamic education to the development of medieval European civilization.